The Impact of Trade Openess on Economic Growth: A Comparative Study of Selected West Africa Countries (1986-2016) - Amedu, Amos Nnaemeka; Ngawu, Umunna Godson (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
The study examined the impact of trade openness on economic growth in some selected countries in West Africa (Ghana, Nigeria, Gambia, Code d’Ivory, Burkina Faso and Sierra Leone). We use the Panel dataset comprising 6 countries from West Africa during this period 1986- 2016. The study used the Fixed effect panel analysis for the estimation. The study tested for descriptive statistics and found that Cote d’ Ivory has the highest trade openness followed by Ghana, Burkina Faso, Nigeria, Sierra Leone and Gambia that has the least trade openness. The study tested for unit root, at first difference 1(I), the variables are stationary, only inflation that was stationary at level I(0). The study uses the Pedroni Co-integration test for long-run association among trade openness, real gross domestic product, foreign direct investment, inflation and exchange rate and found that there exist a long run relationship. The result of the study reveals that trade openness has a positive and significant relationship between gross domestic product, it means that trade openness has an impact to economic growth in the selected West Africa countries.